Perception of allophonic cues to English word boundaries by Japanese second language learners of English - Ito, Kikuyo (Acoustical Society of America, 2009)
Perception of stop aspiration and glottal stop allophonic cues for word juncture in English by Japanese second language (L2) learners of English was examined, extending a study of Spanish L2 learners [Altenberg, E. P. (2005). Second Lang. Res. 21, 325–358]. Thirty Japanese listeners ranging in length of residence (LOR) in the United States (2 weeks–12 years) were tested on 42 contrasting pairs (e.g., aspiration: keeps talking vs keep stalking, glottal stop: a nice man vs an ice man, and double cues: grape in vs grey pin). Phrases were presented in randomly ordered lists and subjects responded in a two-choice identification task followed by a phrase familiarity test. The Japanese listeners performed more poorly than an American English-speaking control group (N=10), especially on aspiration pairs. Aspiration pairs were differentiated significantly less well (73% correct) by Japanese listeners than were glottal stop pairs (91% correct) and double cue pairs (94% correct); response biases predicted from relative familiarity of phrases were evident only for aspiration pairs. Performance correlated with LOR and suggested that aspiration cues take more immersion experience to learn than glottal stop cues. The patterns of errors were similar, but not identical, to Altenberg’s Spanish data.